Financial and Environmental Costs of Manual versus Automated Control of End-Tidal Gas Concentrations. Issue 1 (January 2013) - Tay, S.; Weinberg, L.; Peyton, P.; Story, D.; Briedis, J.
Emerging technologies that reduce the economic and environmental costs of anaesthesia have had limited assessment. We hypothesised that automated control of end-tidal gases, a new feature in anaesthesia machines, will consistently reduce volatile agent consumption cost and greenhouse gas emissions. As part of the planned replacement of anaesthesia machines in a tertiary hospital, we performed a prospective before and after study comparing the cost and greenhouse gas emissions of isoflurane, sevoflurane and desflurane when using manual versus automated control of end-tidal gases. We analysed 3675 general anaesthesia cases with inhalational agents: 1865 using manual control and 1810 using automated control. Volatile agent cost was $18.87/hour using manual control and $13.82/hour using automated control: mean decrease $5.05/hour (95% confidence interval: $0.88–9.22/hour, P =0.0243). The 100-year global warming potential decreased from 23.2 kg/hour of carbon dioxide equivalents to 13.0 kg/hour: mean decrease 10.2 kg/hour (95% confidence interval: 2.7–17.7 kg/hour, P =0.0179). Automated control reduced costs by 27%. Greenhouse gas emissions decreased by 44%, a greater than expected decrease facilitated by a proportional reduction in desflurane use. Automated control of end-tidal gases increases participation in low-flow anaesthesia with economic and environmental benefits.